The nature of money - Quoc, Nguyen Anh (Linguistics and Culture Review, 2021)
In explaining the phenomena of life, thinkers have not clarified the relationship between money and standards and people. Man is a liberty, creative subject, truth in behavior and labor. The product of creative acts creates needs, and the product of labor fulfills human needs. Exchange between people is the exchange of behavior, labor for products as a broker. Relationships between individuals establish standards of ownership of property and people. People, property, and standards are unified, but when the state monopolizes the promulgation of laws and issues money, the state, money, and laws are unified. Laws, money and products exchanged with each other make the relationship between the state and citizens have different functions and tasks. Money is the purpose, so making money to live makes the love of money increase. People forget themselves, become hostile towards each other in the vicious circle of money. When USD became a popular spiritual demand, countries with USD need were in the whirlpool of the money game set by the American regime. Economic growth, war of aggression, defense of the homeland are common spiritual needs. Commodities, modern weapons, arms race, globalization make the USD stronger.